HUBUNGAN BERAT BADAN LAHIR, SINDROM MAKAN MALAM, ASUPAN SERAT, DAN SOSIAL EKONOMI KELUARGA DENGAN STATUS GIZI LEBIH PADA REMAJA USIA 16-18 TAHUN DI SMA NEGERI 6 DEPOK TAHUN 2023 - Salsabila Athirah Putri (2023)
Overnutrition is an excessive amount of body fat that cause various health problems, such as various non-communicable diseases. The prevalence of overnutrition among adolescents aged 16-18 years is 13.5%. In the past 5 years, there has been an increase in the number of overnutrition adolescents aged 16-18 years in Indonesia. This study aims to analyze the risk factors for overnutrition among adolescents aged 16-18 years. The design of this study is a cross-sectional study. The sample in this study consists of 100 adolescents aged 16-18 years in the 10th and 11th grades of SMA Negeri 6 Depok, selected using stratified random sampling. The data analysis used chi-square test and multiple logistic regression. The results of bivariate analysis found a relationship between birth weight (p=0.033;OR=11.9) and night eating syndrome (p=0.001;OR=6.5) with overnutrition, and no relationship was found between fiber intake (p=0.5), parental income (p=0.47), father's education (p=0.25), mother's education (p=0.33), father's occupation (p=0.5), and mother's occupation (0.17) with overnutrition among adolescents in SMAN 6 Depok. The results of multivariate analysis showed that night eating syndrome has a significant association with overnutrition in this study (p=0.002; AOR 6.5; 95% CI 1.9-21.6).